Kokoelma Sara Hildén collection : Ulkomaista nykytaidetta / utlándsk nutidskonst / international Modern Art. (Helsinki : [s.n.])
Alviani, Getulio ; BAcon, Francis ; Bellmer, Hans ; Bill, Max ; Bissier, Jules ; Bissière, Roger ; Botero, Fernando ; Brauner, Victor ; Bravo, Claudio ; Canogar, Rafael ; de Chirico, Giorgio ; Christo ; Close, Chuck ; Dubuffet, Jean ; Farreras, Francisco ; Fontana, Lucio ; Giacometti, Alberto ; etc.
Text Engels-Fins-Zweeds
boek